Impacts of exchange rate and economic, political, cultural, infrastructural, and environmental indicators on tourism in Iran - Sarchami, Ali; Zayandehrodi, Mohsen; Jalaee, Seyyed Abdulmajid (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
Known as the second most profitable industry worldwide, tourism is now very important to states and can have a prominent role in their economic growth. Therefore, it is necessary to analyze the factors affecting tourism. In addition to the exchange rate, these factors include economic, political, cultural, infrastructural, and environmental indicators, all of which were analyzed in this study. For this purpose, a vector autoregressive (VAR) model was developed to analyze data of Iran from 1981 to 2018. According to the research findings, the exchange rate and economic, political, cultural, infrastructural, and environmental composite indicators had significant impacts on Iran’s tourism revenue.